2019
DOI: 10.3389/fimmu.2019.02405
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Mutant Huntingtin Protein in Drosophila Hemocytes Impairs Immune Responses

Abstract: The pathogenic effect of mutant HTT (mHTT) which causes Huntington disease (HD) are not restricted to nervous system. Such phenotypes include aberrant immune responses observed in the HD models. However, it is still unclear how this immune dysregulation influences the innate immune response against pathogenic infection. In the present study, we used transgenic Drosophila melanogaster expressing mutant HTT protein (mHTT) with hemocyte-specific drivers and examined the immune responses and hemocyte function. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
(74 reference statements)
1
7
1
Order By: Relevance
“…The present study examined the role of Drosophila Ado signaling on cytotoxic stress and aimed to elicit the underlying mechanism. Earlier reports have shown that expression of the expanded polyglutamine domain from human mutant huntingtin protein (mHTT) induces cell death in both Drosophila neurons and hemocytes (Marsh et al, 2000;Lin et al, 2019). In our study, we confirmed the low-viability phenotype of mHTTexpressing larvae and observed that such larvae display a lower level of e-Ado in the hemolymph.…”
Section: Introductionsupporting
confidence: 85%
“…The present study examined the role of Drosophila Ado signaling on cytotoxic stress and aimed to elicit the underlying mechanism. Earlier reports have shown that expression of the expanded polyglutamine domain from human mutant huntingtin protein (mHTT) induces cell death in both Drosophila neurons and hemocytes (Marsh et al, 2000;Lin et al, 2019). In our study, we confirmed the low-viability phenotype of mHTTexpressing larvae and observed that such larvae display a lower level of e-Ado in the hemolymph.…”
Section: Introductionsupporting
confidence: 85%
“…In a Drosophila model of the neurodegenerative disease ataxia-telangiectasia, ataxiatelangiectasia mutated (ATM) kinase results in increased AMP gene expression in glial cells, specifically through the NF-κB pathway (Petersen et al, 2012(Petersen et al, , 2013. Also, Drosophila carrying the mutant form of huntingtin, had impaired expression of a few AMPs, including DptB, Attacin, and cecropin A (Table 1), following bacterial infection (Lin et al, 2019), further suggesting a delicate interrelationship between the innate immune system and some of the key proteins in neurodegenerative diseases. The correlative and common elements between AMPs and neurodegenerative diseases warrants further investigation into whether AMPs are the drivers of the diseases, or misregulated as a consequence of the progression of diseases.…”
Section: Implication Of Amps In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The RT-qPCR was performed as previously described (Lin et al, 2019). Total RNA was extracted from adult flies using TRIzol reagent (#1559026, Invitrogen, USA).…”
Section: Real-time Quantitative Reverse Transcription-pcrmentioning
confidence: 99%